Engineering education as a key resource for the development of Industry 4.0 in the East Kazakhstan region - Denissova, O.; Mashekenova, A. (BUKETOV BUSINESS REVIEW, 2024)
Object: to identify current problems in engineering education in the context of the development of Industry 4.0 in the East Kazakhstan region and to develop proposals for its improvement to ensure the region has professionals with corresponding professional competencies. Methods: the search, systematization, and review of scientific literature provided the theoretical basis for the research. The analysis conducted on the basis of data from 2000 to 2022 revealed a relationship between the number of graduates of universities of engineering training and the gross value added per capita of the East Kazakhstan region. An online survey of 187 employers in the region allowed us to determine the level of formation of professional competencies. Interviews with staff, faculty, and students revealed the problems that prevent graduates from obtaining the necessary professional competencies. Findings: elevating the standards of engineering education stands as an essential prerequisite for effectively addressing the imperative of augmenting the technological prowess within the region. The progress of the region hinges not solely on the quantity of graduates in engineering disciplines but also on the caliber of competencies they have acquired. On average, graduates require up to four years to meet employer expectations regarding developed competencies. Given the swiftly evolving technological environment, this timeframe proves excessive, compelling universities to consistently reassess their methodologies for workforce readiness. Conclusions: educational institutions specializing in the training of engineering professionals wield substantial influence in the socio-economic advancement of the region. Integration of the authors’ recommendations for enhancing engineering education into the university management system will streamline the cultivation of adept professionals, fostering sustainable development not only in the East Kazakhstan region but also in other areas of Kazakhstan.